Preparation and Photocatalytic Activity of \(\text{ZnO/TiO}_2\) Hierarchical Heterogeneous Nanostructures via DC Magnetron Sputtering - Quy, Le Phuc; Thu, Vu Thi Hanh (Communications in Physics, 2013)
TiO\(_2\) thin films are used for oxidation of organic radicals, reducing CO\(_2\), skin cancer treatment, decomposing halogen compounds in the air, breaking down surface contaminants, water treatment, biodegradable oil on the surface of the water, disinfect, anti-bacteria, self-cleaning and anti-fog coating,… To increase the photocatalytic and anti-Ecoli bacteria abilities of TiO\(_2\) thin films, this study synthesized the ZnO/TiO\(_2\) hierarchical heterogeneous nanostructures (HNs) by DC magnetron sputtering. The results showed that ZnO/TiO\(_2\) (HNs) has been the photocatalytic and anti - Ecoli bacteria abilities higher than TiO\(_2\) film. This result is explained by reducing the recombination of electrons - holes and slightly shifted absorption edge of them to the visible light band